2019
DOI: 10.1007/s13205-019-1691-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of laccase genes from the basidiomycete Trametes hirsuta Bm-2 and analysis of the 5′ untranslated region (5′UTR)

Abstract: The aim of this study was to identify and characterize laccase genes produced by Trametes hirsuta Bm-2 in a liquid medium, both with and without induction. The amplification of 5′and 3′regions of laccase sequences was obtained by the RACE-PCR method, and these were assembled to obtain a cDNA of total length. Two new laccase genes were isolated from basal medium (lac-B) and lignocellulosic grapefruit substrate (lac-T), both encoding open reading frames of 2566 bp. Both laccase-predicted proteins consisted of 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…For instance, Flammulina velutipes laccases expressed proteins containing 502–670 amino acids (Wang et al 2015b ). Recently, Pereira-Patrón et al ( 2019 ), coded two Trametes hirsuta laccase genes with 521 amino acid sequences, demonstrating a high degree of identity (76–85%) with T. villosa , T. versicolor and other T. hirsuta strains. The authors also identified other characteristics, such as four copper sites and glycosylation sites, common to typical fungal laccases, such as those produced by T. versicolor (Piontek et al 2002 ).…”
Section: Sources Production and Directed Evolution Of Laccasesmentioning
confidence: 99%
“…For instance, Flammulina velutipes laccases expressed proteins containing 502–670 amino acids (Wang et al 2015b ). Recently, Pereira-Patrón et al ( 2019 ), coded two Trametes hirsuta laccase genes with 521 amino acid sequences, demonstrating a high degree of identity (76–85%) with T. villosa , T. versicolor and other T. hirsuta strains. The authors also identified other characteristics, such as four copper sites and glycosylation sites, common to typical fungal laccases, such as those produced by T. versicolor (Piontek et al 2002 ).…”
Section: Sources Production and Directed Evolution Of Laccasesmentioning
confidence: 99%
“…This may because they were isolated from different sources and as laccases are induced by multi-gen families, different types of laccases may be produced in each strain (Thurson, 1994). In a previous study, Pereira-Patrón et al (2019) identified and characterized laccase genes produced by T. hirsute Bm-2 in a liquid medium, with (lac-T) and without (lac-B) induction. Both laccasepredicted proteins consisted of 521 amino acids, 4 copper-binding regions, a signal peptide, and 5 potential glycosylation sites.…”
Section: Decolorization and Phenolic Compounds Degradation Assaysmentioning
confidence: 99%
“…The laccases are enzymes that catalyze the oxidation of various aromatic compounds, specifically phenolic compounds (ortho-and para-diphenols, aminophenols and polyphenols), anilines, polyamines and aryl diamines, as well as some inorganic ions, while concomitantly reducing molecular oxygen to water (España-Gamboa et al, 2017). Three laccases of T. hirsuta Bm-2 were purified and characterized; these enzymes showed high resistance to organic solvents, thermostability, and an ability to decolorize synthetic dyes and textile effluents (Pereira-Patrón et al, 2019). Therefore, this study is focused on the degradation of phenolic compounds and decolorization of biomethanated vinasse, using Trametes hirsuta Bm-2, as well as a comparison with other white rot fungi, analyzing its potential use for the treatment of highly polluting wastewater in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Laccases (EC 1.10.3.2) are a family of copper‐containing oxidases found in a variety of bacteria, fungi, insects, and plants (Baldrian, 2006; Kunamneni et al, 2008; Forootanfar et al, 2011; Martínez et al, 2017). A lot of fungi, ascomycetes, basidiomycetes, and deuteromycetes can produce laccases, but the most efficient laccase producers are white‐rot basidiomycetes (Myasoedova et al, 2017; Patel et al, 2019; Pereira‐Patrón et al, 2019). Until now, more than 100 laccases have been isolated from the fungal cultures and characterized (Baldrian, 2006; Morozova et al, 2007; Chakroun et al, 2010; Sitarz et al, 2016; Glazunova et al, 2019; Patel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%